Penerapan Sistem Informasi Penjualan dan Pemesanan Gerabah Berbasis Web Untuk memudahkan Masyarakat Melakukan Pembelian - Muhammad Wasil; Muhamad Sadali; Muhammad Hamsyuni (Fakultas Teknik Universitas Hamzanwadi, 2023)
Pottery is one of the works of applied art that are that are found in many regions in Indonesia, one of which is fottery in the hamlet of Manggis, Aikdewa village, Pringgasela district. In full also do not have a wide marketing area, because on average they stilluse a conventional system that only relies on the buyer coming home to make purchases and orders for the pottery. The results of pottery crafts are fruit piggy banks, animals, flowers pots, etc selling pottery, then a web-based pottery sales and ordering system was created so that it could be accessed by the wider community, the aim of which was to increase income from these crafts and introduce products online so that they could be accessed anywhere as long as they were connected. Crafts in the hamlet of Dasan Manggis can have an impact on increasing the economy for the community, it can also increase the interest and insight of the younger generation to better understand and understand the process of making the pottery that will be produced.